Prognostic Value of Triglyceride to High-Density Lipoprotein Cholesterol Ratio (TG/HDL-C) in IgA Nephropathy Patients - Pei, Gaiqin; Qin, Aiya; Dong, Lingqiu; Wang, Siqing; Liu, Xiang; Yang, Dandan; Tan, Jiaxing; Zhou, Xiaoyuan; Tang, Yi; Qin, Wei (Frontiers in Endocrinology, 2022)
ABSTRACT: Background: The triglycerides to high-density lipoprotein cholesterol (TG/HDL-C) ratio is an easy-to-use atherogenic and prognostic marker which has attracted increasing attention these days. However, whether TG/HDL-C correlate with outcomes in IgA nephropathy (IgAN) patients remains unknown. To clarify these issues, we conducted this study. Methods: A total of 1149 patients from West China Hospital of Sichuan University were retrospectively analysed between 2008 and 2018.The demographic, clinical and pathological data of all patients at the time of biopsy were collected. Then, patients were divided into the high TG/HDL group (TG/HDL ≥ 1.495, N=383) and the low TG/HDL group (TG/HDL-C < 1.495, N=766) based on the optimal cut-off value of the TG/HDL-C using receive operating curve. Cox proportional hazard models and Kaplan–Meier curves were used to evaluate the renal outcomes of IgAN. Results: The median age of the patients was 33 (26-42) years, and 44.5% were men. By correlation analysis, we found that the TG/HDL-C ratio was negatively correlated with the eGFR (r = 0.248, P < 0.001) but positively correlated with proteinuria (r = 0.229, P< 0.001) and serum uric (r =0.306, P< 0.001). Patients with a higher TG/HDL-C ratio tended to have hypertension [odds ratio (OR), 1.702; 95% CI, 1.298-2.233; P<0.001] and more severe pathologic lesions with tubular atrophy/interstitial fibrosis (OR, 3.593; 95% CI, 2.528-5.107; P<0.001). During a median follow-up period of 54.0 (35.6-73.2) months, a high TG/HDL ratio was strongly associated with worse renal survival in IgAN patients (log-rank: P <0.001). Multivariate Cox analysis demonstrated that a high TG/HDL-C ratio (HR 2.118, 95% CI 1.333-3.367, P=0.002) was an independent predictive marker to ESRD. Conclusion: In this study, we addressed the importance of TG/HDL-C ratio as a predictive marker for IgAN progression.